2012
DOI: 10.3113/fai.2012.0734
|View full text |Cite
|
Sign up to set email alerts
|

Vascularized Pedicle Bone Grafting for Nonunions of the Tarsal Navicular

Abstract: Vascularized pedicle bone grafting is a treatment option for patients with chronic nonunion or osteonecrosis of the navicular. Additionally, it may serve as an adjunct procedure to provide increased vascularity to talonavicular arthrodesis in cases of navicular osteonecrosis and talonavicular arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…For example, non-union of a stress fracture of the tarsal navicular can lead to degenerative joint disease of the talonavicular and naviculocuneiform joints. 140 High-risk stress reactions and stress fractures include those to the pars interarticularis of the spine, the tension side of the femoral neck, the patella, the anterior tibia (the 'dreaded black line'), the medial malleolus, the talus, the tarsal navicular, the metaphyseal/diaphyseal junction of the fifth metatarsal ( Jones' fracture) and the sesamoids. 62 (table 2) The incidence and prevalence of these injuries in children are not well described.…”
Section: Stress Fracturesmentioning
confidence: 99%
“…For example, non-union of a stress fracture of the tarsal navicular can lead to degenerative joint disease of the talonavicular and naviculocuneiform joints. 140 High-risk stress reactions and stress fractures include those to the pars interarticularis of the spine, the tension side of the femoral neck, the patella, the anterior tibia (the 'dreaded black line'), the medial malleolus, the talus, the tarsal navicular, the metaphyseal/diaphyseal junction of the fifth metatarsal ( Jones' fracture) and the sesamoids. 62 (table 2) The incidence and prevalence of these injuries in children are not well described.…”
Section: Stress Fracturesmentioning
confidence: 99%
“…12,21,22 In a study comparing operative with nonoperative treatment, Fitch et al 21 reported successful outcomes with 12 of 16 fractures treated surgically with an average return to sport at 8 months. Overall, 72.2% treated with immobilization or rest with continued weight bearing had worse outcomes with return to activity at 10 months.…”
Section: Treatmentmentioning
confidence: 96%
“…7) and has been an excellent secondary procedure for these difficult patients with avascular necrosis or previous surgery and nonunion. 22 Postoperatively, we place the patient in a bulky Jones dressing for 2 weeks. At 2 weeks, we place the patient into a non-weight bearing cast for 4 more weeks.…”
Section: Author's Recommended Treatmentmentioning
confidence: 99%
“…These local flaps have been used with success for navicular nonunion when a small segment of bone is required and there is minimal surrounding trauma. 12 Our algorithm for free bone flap to the foot and ankle includes the fibula flap and the MFC flap. The MFC flap is used for defects of < 4 cm when structural support is not required.…”
Section: Preoperative Planningmentioning
confidence: 99%
“…Care is then taken to perform a retrograde dissection back toward the dorsalis pedis. The bone flap can then be positioned into the defect 12. …”
mentioning
confidence: 99%